Variation of the antimutagenicity effects of water extracts of Agaricus blazei Murrill in vitro - Guterrez, Z. R.; Mantovani, M. S.; Eira, A. F.; Ribeiro, L. R.; Jordao, B. Q. (Elsevier B.V., 2004)
Agaricus blazei Murill, popularly known as Sun Mushroom or Himematsutake, is native to Brazil. Nowadays, this mushroom has been target of great scientific interest due to its medical power and because it has shown antitumoral and immune modulatory properties. This work evaluated the mutagenic and antimutagenic potential from aqueous extracts prepared in different temperatures (4 degreesC, 25 degreesC and 60 degreesC) from the lineage AB 97/29 in two basidiocarp phases (young and sporulated) and from A. blazei commercialized in Londrina- PR - Brazil, named here as AB PR, and in Piedade- SP- Brazil, named as AB SP. Both micronucleus (MN) as comet assays were used. Chinese hamster lung V79 cells were treated in three antimutagenic experimental protocols: pre-, post- and simultaneous treatments, with the aqueous extracts of the A. blazei Murill and methyl methanesulfonate (MMS). The results suggested that under these circumstances of treatment, aqueous extracts of the A. blazei in both assays did not show any genotoxic potential. However, by the MN test, an antigenotoxic effect was shown against mutagenicity inducted by MMS for aqueous extracts at 60 degreesC of mushroom commercialized in Piedade- SP, in pre-, post- and simultaneous treatments and for AB PR only when used in pre-treatment. on the other hand, with comet assay, the results showed no protective effect in any case. The numbers indicated that different results can be get from A. blazei teas, and that not all of them seemed to be an efficient antimutagen against the induction of micronuclei by MMS. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei; antimutagenicity; micronuclei test; comet assay; V79; methyl methanesulfonate